2003
DOI: 10.1086/376524
|View full text |Cite
|
Sign up to set email alerts
|

Combination and Sequential Antifungal Therapy for Invasive Aspergillosis: Review of Published In Vitro and In Vivo Interactions and 6281 Clinical Cases from 1966 to 2001

Abstract: The development of newer antifungal drugs is creating new potential combination therapies to combat the dismal mortality rate associated with invasive aspergillosis (IA). The efficacy of combination therapy for IA has not been established; sparse data on combination or sequential antifungal therapy depict interactions ranging from synergy to antagonism. We reviewed data from all published in vitro studies, animal model studies, and clinical reports and recent abstracts on combination and sequential antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 282 publications
(230 reference statements)
1
110
0
6
Order By: Relevance
“…In patients with invasive Aspergillus infection who do not improve with a single antifungal agent, consideration should be given to combination antifungal therapy. 8 We hope to heighten the awareness of this often fatal disease and urge prompt and aggressive measures to obtain tissue for diagnosis, and perhaps to start appropriate antifungal treatment even before the diagnosis is made. …”
Section: Discussionmentioning
confidence: 99%
“…In patients with invasive Aspergillus infection who do not improve with a single antifungal agent, consideration should be given to combination antifungal therapy. 8 We hope to heighten the awareness of this often fatal disease and urge prompt and aggressive measures to obtain tissue for diagnosis, and perhaps to start appropriate antifungal treatment even before the diagnosis is made. …”
Section: Discussionmentioning
confidence: 99%
“…The following criteria are commonly followed: synergy, a Ն2-log 10 decrease in CFU/ ml compared to the most active constituent; antagonism, a Ն2-log 10 increase in CFU/ml compared to the least active agent; additivity, a Ͻ2-but Ͼ1-log 10 decrease in CFU/ml compared to the most active agent; and indifference, a Ͻ2-but Ͼ1-log 10 increase in CFU/ml compared to the least active agent. (97,98,130,154,156,211), rats (140), or rabbits (172). Factors that need to be considered while performing in vivo studies include variable drug absorption, distribution, and metabolism among animal species.…”
Section: Methods To Determine the In Vivo Efficacy Of Antifungal Agenmentioning
confidence: 99%
“…Similarly, prior treatment of mice with ITRA abolished the protective effect of AmB, even when ITRA treatment was stopped before AmB therapy was started (199). A recent review of 6,281 clinical cases (from 1966 to 2001) of invasive aspergillosis showed that simultaneous combination and sequential antifungal therapy led to improvement in 63 and 68% of the cases, respectively (211).…”
Section: Dual Combinations In the Practice Guidelines For Aspergillosmentioning
confidence: 99%
“…While it appears that combination antifungal therapy as primary therapy for IA may confer some benefit, this has not yet been rigorously tested in a controlled trial and the decision regarding what combination to use is based primarily on in vitro data, retrospective cohort outcomes, and animal data [102]. Only one, small, prospective randomized trial of combination anti-Aspergillus therapy has been published to date.…”
Section: Aspergillusmentioning
confidence: 99%